2011
DOI: 10.1074/jbc.m111.234559
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ligases Determine Ubiquitination Site and Conjugate Type by Enforcing Specificity on E2 Enzymes

Abstract: Ubiquitin-conjugating enzymes (E2s) have a dominant role in determining which of the seven lysine residues of ubiquitin is used for polyubiquitination. Here we show that tethering of a substrate to an E2 enzyme in the absence of an E3 ubiquitin ligase is sufficient to promote its ubiquitination, whereas the type of the ubiquitin conjugates and the identity of the target lysine on the substrate are promiscuous. In contrast, when an E3 enzyme is introduced, a clear decision between mono-and polyubiquitination is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 65 publications
(85 reference statements)
3
50
0
Order By: Relevance
“…The goal of many E3 ligases is to bring the Ub∼E2 complex into close proximity of the target protein to allow for direct transfer of the ubiquitin from the E2 to the target protein. Recent publications have found that the E3 ubiquitin ligase only enhances substrate ubiquitination, but is not absolutely required [50]. Further, it is distinctly possible that the sequence of the p53-based substrate is similar enough to the sequence on Hdm2 (and Mdm2) to allow for ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of many E3 ligases is to bring the Ub∼E2 complex into close proximity of the target protein to allow for direct transfer of the ubiquitin from the E2 to the target protein. Recent publications have found that the E3 ubiquitin ligase only enhances substrate ubiquitination, but is not absolutely required [50]. Further, it is distinctly possible that the sequence of the p53-based substrate is similar enough to the sequence on Hdm2 (and Mdm2) to allow for ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…E1 enzymes initiate the ubiquitin reaction by ATPdependent activation of ubiquitin and tether it to an E2. The E3 ligases ascertain the specificity of the substrate and facilitate the transfer of this activated complex to the target protein (David et al 2011). Ubiquitin chains established by sequential K48 linkage (polyubiquitination) lead to protein degradation via 26S proteasome, while K63-linked ubiquitin chains regulate signaling (Thrower et al 2000).…”
Section: Ubiquitination Is Critical For Regulating P53mentioning
confidence: 99%
“…As expected, the polyubiquitin-like profile of NUB1 obtained with WT ubiquitin expression was lost with K0 ubiquitin which displayed only the monoubiquitinated form of NUB1 (Fig 3A). Mdm2 is known to catalyze the ligation of K48-linked and K11-linked polyubiquitin chains to p53 [15]. To determine which kind of polyubiquitin chain Mdm2 uses to polyubiquitinate NUB1, we have used K48R and K11R mutants of ubiquitin.…”
Section: Resultsmentioning
confidence: 99%